2009
DOI: 10.1080/01494920902733617
|View full text |Cite
|
Sign up to set email alerts
|

Marital and Parental Relationship Quality and Educational Outcomes for Youth

Abstract: This research examines the effects of parental marital quality and the quality of the parent-child relationship on the educational progress of adolescents. Previous research indicates that family structure and economic capacity have significant effects on educational achievement and high school graduation rates. Few studies, however, examined the effects of the quality of the parental relationship on the educational outcomes of their children. This study is built on bioecological and social capital theories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…These challenges arise in part from complex relationships with stepchildren, former partners, and halfand stepsiblings (Ganong & Coleman, 2004). Third, although children can do well in a variety of family forms, there is some evidence that living in a stepfamily is associated with greater risk for negative outcomes for children when compared with living in a nuclear family (Coleman, Ganong, & Fine, 2000;Ganong & Coleman, 2004;Orthner et al, 2009). This is evidenced more for children and youth in European American families .…”
Section: Introductionmentioning
confidence: 91%
“…These challenges arise in part from complex relationships with stepchildren, former partners, and halfand stepsiblings (Ganong & Coleman, 2004). Third, although children can do well in a variety of family forms, there is some evidence that living in a stepfamily is associated with greater risk for negative outcomes for children when compared with living in a nuclear family (Coleman, Ganong, & Fine, 2000;Ganong & Coleman, 2004;Orthner et al, 2009). This is evidenced more for children and youth in European American families .…”
Section: Introductionmentioning
confidence: 91%
“…The study suggests that children's capacity for development is enhanced by supportive family relationships that encourage human capital development (Orthner et al 2009), and that the quality of the parent-child relationship can have a strong and positive links with participation in postsecondary education among those who graduate from high school.…”
Section: Studies Establishing Association and Sequencementioning
confidence: 99%
“…Many successive large scale, longitudinal studies tracking students from birth to adulthood, have shown a strong association between parental involvement and children's school outcomes across all age ranges (e.g. Bates 2009;Crosnoe et al 2010;Desforges with Abouchaar 2003;Gfellner et al 2008;Hango 2007;Orthner et al 2009). However, the associations are based on passive and post hoc datasets which are not suitable for establishing, rather than speculating on, causal mechanisms (Gorard 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by heightening standards for knowledge acquisition, Orthner et al (2009) posit that the family status and the quality of intra-household relationships are the most fundamental factors behind the educational progress and schooling outcomes of US adolescents.…”
Section: Intergenerational Transmission Of Educational Attainmentmentioning
confidence: 99%
“…While the intergenerational transmission of maternal gender role attitudes toward female labour force participation has received rather limited attention, the intergenerational transmission of human capital accumulation has been scrutinized (Azam and Bhatt, 2015;Blanden, 2013;Chevalier et al, 2013;Conway and Li, 2012;Del Bello et al, 2016;Fessler et al, 2012;Holmlund et al, 2011;Oreopoulos et al, 2003;Orthner et al, 2009;Schneebaum et al, 2015). Holmlund et al (2011) employ Swedish register data to demonstrate a link between the schooling of parents and their descendants due to unobserved genetic transmission, preferences or/and environmental influences.…”
Section: Introductionmentioning
confidence: 99%